PENGARUH UKURAN PERUSAHAAN, STRUKTUR AKTIVA, PERTUMBUHAN PENJUALAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ratna Arsita Sari, 11.05.52.0010; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2015)
The capital structure is the balance or ratio between foreign capital (long-term) with their own capital. This study aimed to analyze the effect of firm size, asset structure, sales growth and profitability of the companys capital structure on LQ-45 Listed in Indonesia Stock Exchange (BEI). The variables studied include company size, strukrur assets, sales growth and profitability. Population in this research are companies registered in LQ-45 company listed on the Indonesia Stock Exchange (BEI). The sampling method used in this research is purposive sampling method. The sample in this study amounted to 98 companies 2011-2013, while the next few samples after normalize to 80 companies. The analysis used is multiple regression analysis were preceded by the classic assumption test consisting of normality test, heteroscedasticity, multicoloniarity test and autocorrelation test. Based on research thathas beenconducted, it was found that the results variebel in fluentialis the size of the company and the asset structure. While that does not affect the growth of sales and profitability of the capital structure.Keywords: Capital Structure, Company Size, Asset Structure, Sales Growth and Profitability